Faktor-Faktor Psikologis Perilaku Phubbing - Gazi Saloom; Ginda Veriantari (Faculty of Ushuluddin and Humanities, 2021)
Phubbing is a common phenomenon in society and, at the same time, is considered inappropriate in social life. This study aims to determine whether social media addiction, boredom proneness, self-control, conformity, and demographic factors affect phubbing behavior. The sample in this study was 387 respondents consisting of active students of UIN Syarif Hidatyatullah Jakarta with probability sampling techniques with simple random sampling techniques. In this study, researchers used an adaptation of a phubbing measuring tool, namely the phubbing scale developed by Karadaǧ (2015), the Bergen Social Media Addiction Scale (BSMAS) developed by Andreassen et al. (2016), boredom proneness Scale-Sort Form (BPS -SF) developed by Vodanovich, Wallace and Kass (2005), self-control scale by Averill (1983), and adaptation conformity scale from measuring instrument developed by Myers (2010). This study indicates a significant influence between social media addiction, boredom proneness, self-control, conformity, and demographic factors on phubbing behavior by 28.7%, while other variables outside of this study influence 71.3%. In addition, three variables significantly influence phubbing behavior, namely social media addiction, self-control, and gender.